Synthesis and antimicrobial activity of some 1,4-disubstituted thiosemicarbazide and 2,5-disubstituted 1,3,4-thiadiazole derivatives - (:unkn) unknown (SOC CHIMICA ITALIANA, 1996)
Various new 1,4-disubstituted thiosemicarbazide and 2,5-disubstituted-1,3,4-thiadiazole derivatives were synthesized and evaluated for their in vitro antimicrobial activity. The structure of compounds was confirmed by elemental analyses and spectroscopic techniques. Some of the synthesized compounds were found to be active against C. Albicans.
Keywords: HETEROCYCLES